IMPLAMETATION OF TEACHING ENGLISH LANGUAGE AS A TEAM STARTEGIES - Y. M. Usmonov; S. D. Abdurakhimova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article we broadly illustrate about teaching strategies in English language a team. Classroom participants communicate many different kinds of information to one another. They talk about the content of the curriculum, the methods they use to learn, and sometimes about the group processes of the class. Frequently, very personal messages with idiosyncratic actions are exchanged, messages that carry special meanings for that particular class.